The rise of the radical right in Iberian countries - Luengo García, Óscar; Fernández García, Ana Belén; Contreras, Ignacio Jesús (My University, 2022)
Spain and Portugal were prominent examples of party systems with no far-right options represented in the Parliament, but something has changed in the last few years. In the April 2019 elections, the Spanish radical right-wing party, Vox, obtained 10.3 per cent of the votes and 24 seats. A few months later, a radical right-wing party, Chega, entered the Portuguese parliament for the first time since the end of the Salazar dictatorship. At present, Vox is the third party in the Spanish parliament in votes and seats after the repetition of the elections in November 2019 while Chega already has 12 seats in the Portuguese parliament after the latest elections held in January of 2022. In addition to parliamentary support for several centre-right governments at the regional level, Vox achieved executive power in one region after agreeing to form a coalition government with the Popular Party in Castilla y León in March 2022. This paper aims to analyse the reasons for the mentioned delay in the representation of those parties and the exceptionalism, if any, of the Iberian cases compared to other countries in Europe. In addition, this paper tries to identify potential differences and similarities between the two Iberian cases. For that, hypotheses from the demand and supply sides will be tested using a comparative approach. This paper argues that the current difference in votes of the radical right in Spain and Portugal is due to the succession of two crises that mobilize identity issues such as national unity and immigration in Spain, especially the first one. This, together with the advance of feminist and LGTBI movements, and the growing political polarization around the country’s authoritarian past, has pushed the political debate in Spain to pivot more around socio-cultural issues than in Portugal, which it is still more focused on socio-economic issues.
The rise of the radical right in Iberian countries
Keywords: Populismo; Derecha (Política); Política comparada - Península Ibérica; Radicalismo; Spain; Portugal; Vox; Chega; Populism; Radical right